Peunajoh.id as a Media for Strengthening Knowledge of Type 2 Diabetes Mellitus Diet Based on Embodied Conversational Agents - Andriani, Rizki; Kamila, Aghnia; Aulia, Yulfa; Harwalis, Harwalis; Afrianti, Novi (Poltekkes Kemenkes Aceh, 2025)
Background: Adherence to the recommended dietary patterns for individuals with Type 2 Diabetes Mellitus (T2DM) is a major challenge in effectively managing the disease. One reason is the varying levels of knowledge among T2DM patients regarding appropriate dietary patterns. Limited knowledge makes it difficult for patients to understand appropriate eating patterns, impacting the effectiveness of diet management. As an educational digital media, the Embodied Conversational Agent (ECA) has proven effective in improving patient knowledge and adherence to T2DM management. Purpose: Developing and evaluating the feasibility of peunajoh.id as an ECA-based application designed to strengthen knowledge of the DMT2 diet. Methods: This study used a Research and Development (R&D) design with the Borg & Gall development model. Validation was conducted by 3 material experts and 3 media experts, followed by an initial trial on 15 T2DM patients in the prolanis community to assess the content's understandability and ease of use of the application, and an operational test on 45 T2DM outpatients to test the effectiveness of the widespread use of ECA media in a regional hospital. Data were analyzed using the Content Validity Index (CVI) to assess the appropriateness of the content and the percentage of user satisfaction with the use of ECA media in dietary education for T2DM patients. Results: Expert validation yielded an average I-CVI of 0.88 (material) and 0.83 (media). The results exceeded the ideal feasibility limit of ≥ 0.78, indicating that the material and media display had high relevance. Operational test results showed an average user satisfaction of 92%, with aspects of ease of navigation at 33.7%, ease of application use at 33.3%, and interaction with virtual agents at 33%. Conclusion: Peunajoh.id is an interesting application and is suitable for use as a diet education digital media for T2DM patients through the results of an average user satisfaction level reaching 92%.